PENGARUH MOBILISASI RANGE OF MOTION (ROM) PASIF TERHADAP WAKTU PULIH SADAR PASIEN DENGAN GENERAL ANESTESI DI RUANG RECOVERY ROOM - Eka Wardani, Aris; Sunanto, Sunanto; Kusyairi, Achmad (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2023)
General anesthesia is a loss of consciousness caused by medicine although the patient receives a stimulus. even with painful stimulus Delayed recovery of consciousness is not expected in anesthesia. Effort that can be made on delayed conscious recovery is passive range of motion (ROM) mobilization, is carried out to teach early mobilization for postoperative patient with general anesthesia. ROM exercises aim to increase muscle strength, prevent stiffness in the press, reduce circulatory disturbances, thereby speeding up recovery time. This study to determine the effect of passive range of motion (ROM) mobilization on the recovery time of patients with general anesthesia in the recovery room of Dr Haryoto Lumajang Hospital. The design of study used the Posttest Only Non Equivalent Control Grup Design, with Accidental Sampling technique. The sample consist of 15 respondents in the intervention group and 15 respondents in the control group. The collecting data used observation. The data analysis used Unpaired T Test. The result of study obtained data on the time to recover consciousness of respondents, mobilized passive ROM, recovered consciousness quickly by 11 (73,3%) respondents and prolonged by 4 (26,7%) respondents. Time to recover consciousness for respondents who did not passive ROM mobilization was all of them recovered consciousness prolonged as many respondents (100,0%). There was an effect of range of motion (ROM) mobilization on the conscious recovery time of patients with general anesthesia in the recovery room of Dr Haryoto Lumajang Hospital with p-value of 0,000 ≤ α = 0.05.